2021
DOI: 10.1093/abt/tbab010
|View full text |Cite
|
Sign up to set email alerts
|

Antibody heavy chain CDR3 length-dependent usage of human IGHJ4 and IGHJ6 germline genes

Abstract: Background Therapeutic antibody discovery using synthetic diversity has been proved productive, especially for target proteins not suitable for traditional animal immunization-based antibody discovery approaches. In recent years, many lines of evidences suggest that the quality of synthetic diversity design limits the development success of synthetic antibody hits. The aim of our study is to understand the quality limitation and to properly address the challenges with a better design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Unsurprising was the bias towards gene family VH3 within the IgG restricted dataset, as VH3 offers a repertoire of increased germline complexity not afforded by other VH segment families. Likewise, the preference towards IGHJ4 falls in line with previous findings and has been suggested to be the result of tyrosine desirability at the CDRH3 locus, by which IGHJ4 contributes two tyrosine residues [33,47]. However, the increased usage of VH5 among Paramyxoviridae, in comparison to the other antigen specificity categories, was striking considering VH5 is comprised of two gene segments, suggesting a potential selective pressure towards the use of VH5 genes in the repertoire against PIV-3 F, as has been implicated for a class of HIV-1 antibodies [48].…”
Section: Discussionsupporting
confidence: 90%
“…Unsurprising was the bias towards gene family VH3 within the IgG restricted dataset, as VH3 offers a repertoire of increased germline complexity not afforded by other VH segment families. Likewise, the preference towards IGHJ4 falls in line with previous findings and has been suggested to be the result of tyrosine desirability at the CDRH3 locus, by which IGHJ4 contributes two tyrosine residues [33,47]. However, the increased usage of VH5 among Paramyxoviridae, in comparison to the other antigen specificity categories, was striking considering VH5 is comprised of two gene segments, suggesting a potential selective pressure towards the use of VH5 genes in the repertoire against PIV-3 F, as has been implicated for a class of HIV-1 antibodies [48].…”
Section: Discussionsupporting
confidence: 90%
“…[30,31] Following these studies, we became interested to developing -hairpin scaffolds that could withhold longer loops (>10-residue long) while closely mimicking the native fold found in antibodies. In comparison to all CDRs, H3 loops are known to possess the largest variability in sequence [32,33] and length (4 up to >21 residues) [34] which drastically increases the span of conformational space generated [35,36] to maximize bounded states. [37][38][39][40] The vast majority of CDR-H3s possess a -bulge motif edging the loops [41,42] , yet the role played by this motif in the hairpin thermodynamic stability and scaffold rigidification remain largely unexplored.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that NGS has four main applications in antibody phage display: library quality control, analysis of selection outputs, reconstruction of low-frequency clones, and rationale design based on natural repertoires ( Ravn et al, 2010 ; Zhang et al, 2011 ; Mahon et al, 2013 ; D'Angelo et al, 2014 ; Glanville et al, 2015 ; Yang et al, 2017 ; Jian et al, 2019 ; Valadon et al, 2019 ; Azevedo Reis Teixeira et al, 2021 ; Wang et al, 2021 ), which have resulted in some FDA approved antibodies ( Alfaleh et al, 2020 ). In this work, we used NGS information for identifying and reconstructing low-frequency clones with less-frequent CDRH3 lengths, for studying the pairing between CDRL3 and CDRH3 lengths in the selection output, and for fine-tuning the library length diversity.…”
Section: Discussionmentioning
confidence: 99%